Opportunities for NCD screening and control efforts among people living with HIV/AIDS attending care and treatment clinic at a regional referral hospital in Dar es Salaam - Atuganile Musyani; Grace Mosi; Erik Kinyenje; Mucho Mizinduko; Rogath Kishimba; Meshack Shimwela; Leonard Subi (Bulletin of the National Research Centre)
Abstract Background Persons living with human immunodeficiency virus (PLHIV) in Tanzania now live longer and hence are at increased risk of developing noncommunicable diseases (NCDs). Despite many resources committed to HIV care programs, NCD care remains inadequately integrated into these programs. This study aimed to describe risk factors and evaluate control rates of three months of NCD preventive efforts among PLHIV attending the care and treatment clinic (CTC) at Temeke Regional Referral Hospital (RRH). Methods The study employed a mixed-method approach, including a cross-sectional study to identify hypertension risk factors and pre–post-intervention follow-ups to assess NCD control rates among PLHIV. Conducted between January and June 2020, the study included interviews, secondary data reviews, and screening for blood pressure and blood glucose levels using the World Health Organization STEPS surveillance tool. Data were analyzed using STATA, employing logistic regression to determine NCD risk factors. The intervention enrolled patients diagnosed with hypertension, increased blood glucose, or both to receive NCD preventive health education. Blood pressure and glucose levels were re-evaluated after three months using a paired t-test to assess control rates. Results The interview was conducted with a total of 333 PLHIV, of whom 71 (21.32%) were diagnosed with hypertension and 9 (2.70%) had elevated blood glucose levels. Notably, 177 (53.15%) participants had never had their blood pressure measured before, and 37 (20.90%) of them were newly diagnosed with hypertension. The intervention cohort included 76 patients, of whom 71 had hypertension. After the intervention, 26 (36.6%) patients achieved blood pressure control. Of the nine patients with elevated blood glucose, 5 (55.5%) had normalized levels. Conclusion Undiagnosed NCDs are highly prevalent among PLHIV attending CTC at Temeke RRH. Targeted interventions show the potential to improve NCD outcomes. Integrating NCD care into existing HIV programs could enhance the health longevity of PLHIV.